The power of the word in arabic and hebrew proverbs - Degani, Amiram (Anaquel de Estudios Árabes, 2004)
The oriental cultures recognize the enormous power of the word. Words can create and change realities, cause irreparable damage, or, on the other hand, “open gates of iron”. In this article a corpus of around 100 Arabic and Hebrew proverbs is presented, that treat the Power of the Word. They advise man to be prudent in his speech or even to keep silent. Furthermore, in the first part we treat the importance of the correct and beautiful expression, or the aesthetics of the words, especially in the frame of the Arabic culture.